404 REPEATED STRESS MAY ALTER THE ABILITY OF NICOTINE TO ACTIVATE THE HYPOTHALAMIC-PITUITARY ADRENAL AXIS. (1st January 2005) - Brown, M. C.; Lutfy, K.; Tran, B.; Friedman, T. C.
Abstract : Objective: The hypothalamic-pituitary adrenal (HPA) axis is intimately involved in the stress response. Similar to other stressors, acute nicotine administration has been shown to stimulate ACTH and corticosterone/cortisol secretion in both rodents and humans, raising the possibility that activation of the HPA axis by nicotine may mediate some of the effects of nicotine. We hypothesized that chronic stress increases the ability of nicotine to activate the HPA axis and that the nature of the stress (mild vs. severe) may be critical in subsequent activation of the HPA axis by nicotine. Method: Male C57/BL6 mice (25 g, 8 wks old) were exposed to one of the two stressors (swim in 15°C or 32°C for 3 min/day for 5 days). Controls were not exposed to either stressor. On day 8, half of the mice in each group received saline and the other half received nicotine (0.5 mg/kg, s.c.). Fifteen min later, the mice were then sacrificed, trunk blood was collected and assayed for levels of ACTH and corticosterone using radioimmunoassays. Results: Acute exposure to either stressor increased serum ACTH and corticosterone levels. Similarly, as compared to saline, nicotine injection increased the level of corticosterone and ACTH. While there was no significant difference in basal ACTH and corticosterone level in stressed groups as compared to non-stressed controls, the group subjected to the severe stressor (swim in 15°C water), had significantly higher levels of ACTH in response to an acute nicotine challenge (15°C = 86.8 pg/mL, 32°C = 54.5 pg/mL, control= 48 pg/mL). Conclusion: These results confirm our hypothesis that chronic stress leads to an enhanced sensitivity of the HPA axis to a nicotine challenge and that the severity of the stress is important in this regard. The present results may help to understand how stress may increase the risk of nicotine use and possibly help in the design of novel treatments for nicotine addiction.